2017
DOI: 10.7150/jca.21401
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of lung metastases in a murine breast cancer model reveals divergent influence of CTSB and CTSL overexpression

Abstract: Studies in the MMTV-PyMT (PyMT) breast cancer mouse model have shown a strong influence of the lysosomal cysteine cathepsins B or L on lung metastasis formation. Transgenic expression of human CTSB (tgCTSB) or CTSL (tgCTSL) both led to similar metastatic phenotypes with increased metastatic burden in the PyMT mice. However, recent studies in other tumor models proved marked differences in effects of either cathepsin on the proteome composition. We sought to analyze and compare proteome changes in the metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
(73 reference statements)
0
9
1
Order By: Relevance
“…CTSL is the main member of the lysosomal cysteine protease family. CTSL can hydrolyze proteins, plasma proteins, hormones, and phagocytic bacteria by activating CTSB (38). The present study found that S. aureus infection of MAC-T did not affect the expression of CTSD but inhibited that of CTSL.…”
Section: Discussioncontrasting
confidence: 38%
“…CTSL is the main member of the lysosomal cysteine protease family. CTSL can hydrolyze proteins, plasma proteins, hormones, and phagocytic bacteria by activating CTSB (38). The present study found that S. aureus infection of MAC-T did not affect the expression of CTSD but inhibited that of CTSL.…”
Section: Discussioncontrasting
confidence: 38%
“…Abnormal activity of Cts B or Cts L however was implicated in several pathologies including tumorigenesis, cardiovascular diseases and Parkinson's disease (1012). Therefore, several attempts have already been made to gain better insights into their exact molecular functions and their targets in different physiological conditions (1315). In the context of cell metabolism, a seminal study by Prudova et al , for example, recently managed to identify a novel Cts B cleavage site in the Pyruvate kinase M2, a rate-limiting enzyme in glycolysis pathway, thereby providing a mechanistic link between cathepsin activity and glycolysis in pancreatic cancer cells (10).…”
mentioning
confidence: 99%
“…Previous studies have showed that CTSL expression is associated with the prognosis of tumor patients. For example, CTSL is over expression in nasopharyngeal carcinoma, breast cancer and pediatric acute myeloid leukemia, and is associated with poor disease-free survival (9,10). In this study, Kaplan-Meier survival analysis showed that patients with high CTSL levels had shorter OS and worse prognosis.…”
Section: Discussionmentioning
confidence: 58%
“…This extracellular proteolytic activity encourages the invasion of cancer cells into surrounding tissues, blood and lymphatic vessels, and the metastasis of tumor tissue to distant tissues. Studies have shown that the expression of CTSL signi cantly increases in lung cancer, gastric cancer, ovarian cancer, breast cancer, glioma and other malignant tumors, and it promotes the proliferation, invasion, migration, drug resistance and angiogenesis of tumor cells and other malignant biological behaviors (9,10). Yu et al found that the over-expressed transcription factor Forkhead box O3a (FOXO3a) in gastric cancer cells can increase the activation of the CTSL promoter, inhibit the expression of E-cadherin, and promote gastric cancer (11).…”
Section: Introductionmentioning
confidence: 99%